Pancreatic islet transplantation. - Johnson, P; Jones, K (2012)
Pancreatic islet transplantation is a minimally invasive treatment that has the potential to prevent diabetes after total pancreatectomy for benign disease (islet autotransplantation) and to reverse diabetes in those with type 1 diabetes (islet allotransplantation). In both scenarios, the treatment involves extracting sufficient numbers of pancreatic islets from the resected or donor pancreas and infusing these through the portal vein into the patient's liver. The results for both forms of this treatment have been encouraging over recent years, with up to 85% of adult patients remaining insulin independent for at least 1 year after transplantation. However, there are a number of challenges that need to be overcome before these treatments can be used routinely in children. The aim of this review is to outline the rationale, methodology, and current results of islet allotransplantation, and to discuss the potential new developments that could enable this important treatment to be widely applicable to children. Although islet autotransplantation is not discussed in detail, the overall rationale and methods are similar. However, as the procedure involves the transplantation of the patient's own islets, and the indication for the procedure is not for autoimmune disease, there are none of the difficult immune challenges of allotransplantation.